Entrepreneurship Capital: A Regional, Organizational, Team, and Individual Phenomenon - David B. Audretsch; Erik Monsen (Max Planck Institute of Economics, 2007)
We review the role entrepreneurship capital in regional economic performance and extend it to explain the economic and entrepreneurial performance of organizations, teams, and individuals. Drawing on entrepreneurship and social capital research, we demonstrate that researchers at different level of analysis are in fact modeling the same underlying multi-level concept: entrepreneurship capital. We identify elements of entrepreneurship capital at and across the levels. Where there are gaps, we suggest new directions for research, public policy, and management practice that focus on enhancing organizational, interpersonal, and personal factors which promote entrepreneurial action at and across regional, organizational, team, and individual levels.
Keywords: 330; Entrepreneurship; Social Capital; Multilevel; Unternehmer; Social Capital; Regionale Entwicklung; Wachstumstheorie; Wissenstransfer; Spillover-Effekt; Theorie